Respuesta :
Answer:
Option D. - 59
Step-by-step explanation:
To solve this problem the first step is to introduce the function g(x) inside the function f(x). Therefore the range of g(x) will now be the domain of f(x).
f(x) = -2x - 7
g(x) = -4x + 6
(f o g)(x) = f(g(x))
f(g(x)) = -2(-4x + 6) - 7
f(g(x)) = 8x -12 -7
f(g(x)) = 8x -19
Now we make x = -5
(f o g)(- 5) = 8 (-5) -19
(f o g)(- 5) = -59
The correct option is D. -59
Answer:
Option D. -59 is the correct answer.
Step-by-step explanation:
The given function in the question are f(x) = -2x - 7 and g(x) = -4x + 6
Then we have to find the value of (f o g)(-5).
So we will find the function (f o g)(x) first.
(f o g)(x) = -2(-4x + 6) - 7 = 8x - 12 - 7
= 8x - 19
Now (f o g)(-5) = 8×(-5) - 19 = -(40 + 19) = -59
Therefore the value of (f o g)(-5) = -59.
Option D is the correct answer.